Development of Prophetic Intelligence (Phenomenology Study of Religious Transformation) - Ahmad Sultoni; Alef Theria Wasim; Aris Fauzan (International Journal of Islamic Educational Psychology, 2020)
This research is a study of the process and results of Prophetic Intelligence development conducted by Kalong students (students who are not staying in the school) in the Roudhotul Muttaqien Islamic boarding school led by KH Hamdani Bakran Adz Dzakiey. This type of research is qualitative research design with Phenomenology Study. Data collection techniques used involved observation, interview, and documentation. Qualitative data analysis used Interpretative Phenomenology Analysis (IPA) and Validity testing used triangulation and reflection. The results of this study are; 1) there are several transformation phases of the mystical experience of the kalong student with three sequences, a) Pre-transformation process in the desire to feel the essence of worship, b) the process of transformation in the derive of mystical experience towards Allah, and c) Post-transformation process that describes changes in a more religious mindset and more polite behavior and gives benefit to the surrounding. The mastery of prophetic intelligence by  kalong student is grouped in two ways; a) mastery of quantitative competencies, including mastery of intellectual intelligence, spiritual intelligence, emotional intelligence, and perceptual intelligence in a prophetic perspective, b) mastery of qualitative competencies in accordance with the essence of prophetic intelligence, such as turning the body into a light that shows the attainment of clarity of heart, obtaining abilities that had not previously been studied (getting Laduni's knowledge).